5. CLINICAL, PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF ACUTE DRUG POISONING PATIENTS AT THE EMERGENCY DEPARTMENT OF TRANSPORT HOSPITAL, 2022–2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical, paraclinical characteristics and treatment outcomes of acute drug poisoning at the Emergency Department of Transport Hospital.Methods: A retrospective cross-sectional study was conducted on 48 patients aged ≥18 years admitted between January 2022 and September 2023. Variables included demographics, type of toxic agents, clinical manifestations, laboratory results, electrocardiographic abnormalities, management strategies, and discharge outcomes. Data were analyzed using SPSS 20.0 with statistical significance set at p
Keywords: acute poisoning, paracetamol, pharmaceuticals, clinical characteristics, treatment outcomes